Ras/Raf/MEK/ERK Pathway Activation in Childhood Acute Lymphoblastic Leukemia and Its Therapeutic Targeting - Knight, Thomas; Irving, Julie Anne Elizabeth (Frontiers in Oncology, 2014)
Deregulation of the Ras/Raf/MEK/ERK pathway is a common event in childhood acute lymphoblastic leukemia and is caused by point mutation, gene deletion and chromosomal translocation of a vast array of gene types, highlighting its importance in leukemia biology. Pathway activation can be therapeutically exploited and may guide new therapies needed for relapsed ALL and other high risk subgroups.